Genome reduction in Paenibacillus polymyxa DSM 365 for chassis development - Ravagnan, Giulia; Lesemann, Janne; Müller, Moritz-Fabian; Poehlein, Anja; Daniel, Rolf; Noack, Stephan; Kabisch, Johannes; Schmid, Jochen (Frontiers in Bioengineering and Biotechnology, 2024)
The demand for highly robust and metabolically versatile microbes is of utmost importance for replacing fossil-based processes with biotechnological ones. Such an example is the implementation of Paenibacillus polymyxa DSM 365 as a novel platform organism for the production of value-added products such as 2,3-butanediol or exopolysaccharides. For this, a complete genome sequence is the first requirement towards further developing this host towards a microbial chassis. A genome sequencing project has just been reported for P. polymyxa DSM 365 showing a size of 5,788,318 bp with a total of 47 contigs. Herein, we report the first complete genome sequence of P. polymyxa DSM 365, which consists of 5,889,536 bp with 45 RNAs, 106 tRNAs, 5370 coding sequences and an average GC content of 45.6 %, resulting in a closed genome of P. polymyxa 365. The additional nucleotide data revealed a novel NRPS synthetase that may contribute to the production of tridecaptin. Building on these findings, we initiated the top-down construction of a chassis variant of P. polymyxa. In the first stage, single knock-out mutants of non-essential genomic regions were created and evaluated for their biological fitness. As a result, two out of 18 variants showed impaired growth. The remaining deletion mutants were combined in two genome-reduced P. polymyxa variants which either lack the production of endogenous biosynthetic gene clusters (GR1) or non-essential genomic regions including the insertion sequence ISPap1 (GR2), with a decrease of the native genome of 3.0 % and 0.6 %, respectively. Both variants, GR1 and GR2, showed identical growth characteristics to the wild-type. Endpoint titers of 2,3-butanediol and EPS production were also unaffected, validating these genomereduced strains as suitable for further genetic engineering.